Current advances of murine models for food allergy. (February 2016) - Liu, Tiange; Navarro, Severine; Lopata, Andreas L.
Highlights: Mouse models are essential platforms for food allergy studies. The establishment of mouse models can be influenced through different parameters. The development of mouse models provides valuable insights into food allergenicity, therapies and allergic inflammation mechanisms. Many milk, peanut and shellfish allergens have not been evaluated using murine models. Abstract: Food allergy affects an increasing population in Western world but also developing countries. Researchers have been taking great efforts in identifying and characterising food allergens using molecular tools. However, there are still many mechanistic hypotheses that need to be tested using an appropriate in vivo experimental platform. To date, a number of mouse models for food allergy have been established and provided valuable insights into food allergenicity, development of therapies and allergic inflammation mechanisms. Nevertheless, a large diversity of protocols have been developed for the establishment of relevant mouse models. As a result, comparisons of outcomes between different models are very difficult to be conducted. The phenotypes of mouse models are greatly influenced by genetic background, gender, route of allergen exposure, the nature and concentration of food allergens, as well as the usage of adjuvants. This review focuses on IgE-mediated food allergy, compares the differential approaches in developing appropriate murine models for food allergy and details specific findings for three major food allergens, peanut, milk and shellfish.